Shelved under murder ebook - Gilbert, Victoria (Blue Ridge Library Mystery, 2018)
Autumn leaves aren’t the only things falling in the historic Virginia village of Taylorsford—so are some cherished memories, and a few bodies October in Taylorsford, Virginia means it’s leaf peeping season, with bright colorful foliage and a delightful fresh crew of tourists attending the annual Heritage Festival which celebrates local history and arts and crafts. Library director Amy Webber, though, is slightly dreading having to spend two days running a yard sale fundraiser for her library. But during these preparations, when she and her assistant Sunny stumble across a dead body, Amy finds a real reason to be worried. The body belonged to a renowned artist who was murdered with her own pallet knife. A search of the artist’s studio uncovers a cache of forged paintings, and when the sheriff’s chief deputy Brad Tucker realizes Amy is skilled in art history research, she’s recruited to aid the investigation. It doesn’t seem to be an easy task, but when the state’s art expert uncovers a possible connection between Amy’s deceased uncle and the murder case, Amy must champion her Aunt Lydia to clear her late husband’s name. That’s when another killing shakes the quiet town, and danger sweeps in like an autumn wind. Now, with her swoon-inducing neighbor Richard Muir, Amy must scour their resources to once again close the books on murder in Shelved Under Murder , the charming second installment in Victoria Gilbert’s Blue Ridge Library mysteries, perfect for fans of Jenn McKinlay and Miranda James.